Comparative analysis on friction characteristics between free-piston engine generator and traditional crankshaft engine. (1st October 2021) - Li, Jian; Zuo, Zhengxing; Jia, Boru; Feng, Huihua; Wei, Yidi; Zhang, Zhiyuan; Smallbone, Andrew; Paul Roskilly, Anthony
Highlights: Detailed friction models of each component in FPEG and TCE are presented. Dynamic and friction characteristics of FPEG and TCE are compared and analyzed. Effects of lubricating oil viscosity and temperature on friction loss are studied. Total mean friction power in FPEG is obviously lower than that in TCE. Abstract: Compared with traditional crankshaft engines (TCEs), free-piston engine generators (FPEGs) present many potential advantages due to the abandonment of crankshaft mechanism. The friction loss in FPEGs is considered to be lower than that in TCE. However, few studies have calculated and analyzed the friction differences between them in any great detail. This paper presents an equivalent design of two-stroke TCE based on an existing FPEG prototype size, and then determines the main friction components of their prototypes. The comprehensive simulation models of FPEG and TCE are established in MATLAB/Simulink. Following this, the friction models and lubrication characteristics of each part in FPEG and TCE are described and compared based on the fundamental lubrication theory. The simulation results show good agreement with the experimental data for both the cold start and combustion power generation. And the overall error between them is less than 5%, indicating that the simulation model is reliable and can predict the prototype performance. Moreover, the effects of lubricating oil grade, temperature and operating frequency on the friction performance of FPEG are also investigated. Results show that the piston assembly friction power is less powerful in FPEG (118.3 W) than that in TCE (142.1 W), while the friction power of piston rings is slightly more powerful in FPEG than TCE. The total mean friction power is significantly lower in FPEG than that in TCE, with the proportion of total mean friction power to the indicated power being 11% in TCE and 6.7% in FPEG. This distribution of friction power indicates that when concerning friction loss, FPEG has an advantage over TCE. The piston ring friction power increases with an increase in lubricating oil temperature and operating frequency, and decreases with an increase in lubricating oil viscosity. The proportion of mean friction power to the indicated power shows a decreasing trend as the viscosity and operating frequency increase, and an increasing trend as the lubricating oil temperature increases.